Personality traits and their relationship with oral health related quality of life among adolescents in Saudi Arabia - Danah Sahmi Alhajri; Danah Abdullatif Alhammad; Lulwah Fouad Alabdulqader; Reem Rashed Alasbly; Muhanad Alhareky; Mazin Algahtani; Asim Al-Ansari; Muhammad Ashraf Nazir (BMC Oral Health)
Abstract Background Personality traits are linked with different oral health outcomes. However, personality traits and their associations among children are not fully understood. Therefore, this study aimed to investigate the relationship between personality traits and oral health-related quality of life (OHRQoL) among adolescents in Saudi Arabia. Methods This cross-sectional study included male and female students aged 12–18 years from different schools in the Eastern Province of Saudi Arabia. The participants responded to a self-administered questionnaire after providing informed consent. The questionnaire included demographic information and Arabic versions of the Big Five Personality Inventory and the Child Oral Health Impact Profile-Short Form to evaluate personality traits and OHRQoL, respectively. Bivariate and multivariable analyses were performed. Results This study included 231 (59.7%) males and 156 (40.3%) females. Regarding personality traits, conscientiousness had the highest mean score (15.31 ± 3.65), followed by agreeableness (14.94 ± 3.96) and openness (14.08 ± 3.98), whereas neuroticism had the lowest mean score (8.86 ± 3.34). Males had significantly higher mean scores for extraversion (14.28 ± 3.30) and conscientiousness (15.69 ± 3.62) compared to females, who had mean scores of 13.02 ± 3.35 and 14.75 ± 3.63, respectively (P < 0.05). Females, on the other hand, scored significantly higher in neuroticism (9.51 ± 3.71) and agreeableness (15.60 ± 3.75) compared to males, who had mean scores of 8.09 ± 2.94 and 14.49 ± 4.04, respectively (P < 0.05). Bivariate analyses showed that neuroticism was negatively correlated with OHRQoL (r = -0.455, P < 0.001), whereas extraversion (r = 0.182, P < 0.001) and conscientiousness (r = 0.110, P = 0.047) were positively correlated with OHRQoL. In multiple linear regression analyses, extraversion (B = 0.696, P = 0.012) and neuroticism (B=-2.229, P < 0.001) were statistically significant predictors of OHRQoL. Conclusion This study found that neuroticism was significantly and negatively correlated with OHRQoL, whereas extraversion was significantly and positively correlated with OHRQoL. In addition, there were statistically significant differences in personality traits between the male and female adolescents.